Imaging-guided pre-dilatation, stenting, post-dilatation: a protocolized approach highlighting the importance of intravascular imaging for implantation of bioresorbable scaffolds. (3rd June 2018) - Ali, Ziad A.; Karimi Galougahi, Keyvan; Shlofmitz, Richard; Maehara, Akiko; Mintz, Gary S.; Abizaid, Alexandre; Chamié, Daniel; Hill, Jonathan; Serruys, Patrick W.; Onuma, Yoshinobu; Stone, Gregg W.
ABSTRACT: Introduction : The advent of the fully bioresorbable vascular scaffold (BVS) is the latest step in a series of advancements in the design of intracoronary stents over the past few decades. The novelty of this technology is in providing temporary vessel scaffolding and local antiproliferative therapy to prevent neointimal hyperplasia after percutaneous coronary intervention followed by gradual resorption of the scaffold to restore the native vessel anatomy and physiology – a process termed vascular reparative therapy. Areas covered : The first generation of BVS has not been able to fully match the high benchmark in safety and efficacy set by contemporary metallic drug-eluting stents. These shortcomings of BVS may be due to factors related to the device itself, the complexity of the underlying lesion, or the implantation technique. Expert commentary : Here, how intravascular imaging may be used to minimize these shortcomings is described and moreover, an imaging-guided step-by-step approach for BVS implantation that integrates the recently described pre-dilatation, stenting, post-dilatation (PSP) strategy is explained.